Jugamos con las palabras creando rimas - Leiva Espinola, Tania Lizet (2020)
This demonstrative learning session: “We play with words creating rhymes”, to be executed with children of 05 years of the initial education level of Regular Basic Education, has as its learning purposes the development of the competition “Communicates orally in their mother tongue” combining capabilities such as: Obtains information from the oral text, infers and interprets information from the oral text, adapts, organizes and develops the text in a coherent and cohesive way, uses nonverbal and para verbal resources strategically, interacts strategically with different interlocutors and reflects and evaluates the form, content and context of the oral text. It also responds to the performance “Participate in conversations, dialogues or listen to stories, legends, rhymes, riddles and other stories of the oral tradition. He waits for his turn to speak, listens while his interlocutor speaks, asks and answers about what he is interested in knowing or what he has not understood with the intention of obtaining information”. In this context, it assumes a socioconstructivist pedagogical position within the framework of the competency curriculum is configured with the didactic processes of the Communication area according to the communicative approach in the framework of the social practices of the language and is oriented with the formative evaluation within the paradigm Intercultural humanist education that promotes the Peruvian State.